(untitled) (Abstracta, 2024)
Artigos publicados - P017-2024 à P056-2024 Defesas de Dissertações do IFGW - D007-2024 à D10-2024 Defesas de Teses do IFGW - T004-2024 à T006-2024 Defesas do PECIM - P002-2024